(untitled) (Global Journal of Medical Research, 2021)
The provision of qualified care to patients with congenital cleft of the upper lip and palate (CCLP), accompanied by dentoalveolar anomalies and nasal deformities is one of the most difficult tasks of modern dentistry and maxillofacial surgery . According to various authors, complications after reconstructive operations range from 8 to 32% (4,5,8,13,14). In this pathology, the quality of the postoperative scar depends on the general condition of the body, the nature of the disease, the experience of the surgeon, the type of suture material and many other factors. Any surgical intervention in the dento-maxillary system causes disturbances in microcirculation, as well as blood circulation of tissues around the wound, which leads to an inflammatory reaction. Even with the initial wound healing, accompanied by a decrease in blood supply, the scar forms and matures more slowly, and its quality is worse. The interest in the problem of postoperative wound healing is explained by the fact that inflammation plays a leading role in the course of any wound process, which determines the path along which wound healing will go.